Building Community Resilience to Disasters A Way Forward to Enhance National Health Security - Chandra, Anita (RAND Corporation, 2011)
Community resilience, or the sustained ability of a community to withstand and recover from adversity, has become a key policy issue. This report provides a roadmap for federal, state, and local leaders who are developing plans to enhance community resilience for health security threats and describes options for building community resilience in key areas.